(untitled) (Fiep Bulletin - online, 2013)
The inclusion of students with disability in the classes of Physical Education is a reality; however, the application of the guidelines proposed by different education systems has been one of the major problems for school exclusion. For this reason, with the biggest presence of people with deficiency in the school system, the current study had as goal to investigate the meanings attached to inclusion from the teachers’ perspective in order to learn about their pedagogical strategies. These teachers work in regular schools in the Municipal and State education system at Minas Gerais, in Brazil. In the total 143 physical education teachers have participated in this study. They were from seven different cities and schools in the state of Minas Gerais. The results indicated that the sport proposals, especially, have encouraged and intensified the exploitation of the possibilities of bodily movements starting from standardized and adapted movement. As a consequence, “differentiated bodies” are conquering new social spaces. It indicates that a work that is able to respect individuality and that makes use of a cooperation perspective is still a difficulty for the professionals of this domain. The most important is to challenge the rigid models of competitive sport and the sport professionals in order to act in a new person, sporting and social construction of the students handicapped.